MUTUAL RELATIONSHIP BETWEEN THE GENDER DIFFERENCES AND FUNCTIONAL ASSYMETRY OF THE HEAD’S HALF LOBES OF CHILDREN - Mansurova Surayyo Ravshanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
It can be assumed that the organization of education, taking into account the “subtle” link between the age periods of gender differences in preschool children and the formation of the head brain – is one of the important factors of successful socialization of the child’s personality. Improper exposure to this process can adversely affect the child’s psychological development, resulting in the development and behavior of the child with various deviations.